Preventing Theft in Kemiri Village: Collaboration Between Sectoral Police and Village Government - Abraham, Abraham; Agustin, Windi; Arifa, Masyitha Aulia; Sulistianingsih, Dewi (Faculty of Law Universitas Negeri Semarang, 2023)
This study discusses the role of the village government and the role of the surrounding community in implementing an environmental protection system. The purpose of writing this article is to find out data related to security and public order in Kemiri Village. This article is descriptive review supported by qualitative data that aims to reveal the facts or reality of certain social phenomena and provide an objective description of the conditions or problems that may be encountered. Then knowing this, actually, what can the village government do in an effort or at least minimize the crime rate, especially theft in the village of Kemiri? Field data and facts were obtained directly from informants through observation, namely parties who know the information needed regarding environmental safety in the Kemiri Village environment, Kaloran District, Temanggung Regency. As a result authors find out that between the Government, The villagers and The Police cooperate to overcome the situation, but in fact not all problems in society can be solved especially concerning thievery. In conclusion the reason why there is still a crime of theft, especially in the village of Kemiri the security facilities which are inadequate and not as modern as in a big city, also some of villagers careless of their belongings and Lack of police personnel.